PROTEIN FROM BLANCH LIQUOR - VENUGOPALAN, V; CHAKRABORTY, P K; JAMES, M ARUL; GOVJNDAN, T K (Fishery Technology, 2025)
A pr.ocess is described for isolation of edible protein from blanch liquor, which is discarded as a waste at present from prawn canning factories. The protein isolated is colourless and odourless and contains an appreciable amount of salt from the brine used for blanching prawns. It is comparable to fish protein concentrate in amino acid composition.